2011
DOI: 10.1111/j.1442-9993.2010.02132.x
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies interactions among a plant parasite, a pollinator and a seed predator affect the reproductive output of an invasive plant, Cytisus scoparius

Abstract: Interactions between species pairs are almost always mediated by interactions with other species. The outcomes of these multispecies interactions are often difficult to predict and are rarely studied. In addition to their theoretical importance, multispecies interactions are also important for management situations. Where multiple agents are used to control invasive species, interactions between agents may either enhance or reduce the impacts on the target species, or may simply have additive effects. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Similar evidence of chronic photoinhibition has been reported for another invader, Cytisus scoparius, when infected with C. pubescens (Shen et al, 2010). Control of U. europaeus and C. scoparius by C. pubescens could complement biological control using phytophagous insects (Prider et al, 2011).…”
Section: Parasitic Plants Attacking Invasive Species: the Empirical Evidencesupporting
confidence: 66%
“…Similar evidence of chronic photoinhibition has been reported for another invader, Cytisus scoparius, when infected with C. pubescens (Shen et al, 2010). Control of U. europaeus and C. scoparius by C. pubescens could complement biological control using phytophagous insects (Prider et al, 2011).…”
Section: Parasitic Plants Attacking Invasive Species: the Empirical Evidencesupporting
confidence: 66%
“…The differences between these treatments suggest that the effects of prior interactions depend not just on the identity of the antagonist (i.e., herbivore vs. parasite), but also on the outcome of the interaction. Given that prior parasite attachment can reduce subsequent herbivory and deter pollinators [ 46 ], we suggest experiments testing whether these two dodder induction treatments vary in their effects on subsequent herbivore attraction, pollinator attraction, and fruit yield. Although tomato plants are largely self-fertile, pollinators are required to yield fruit [ 47 ], so the effects of parasites on pollinators are particularly relevant in agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Since seasonal sensitivities increase in the spring and allergic reactions occur in sensitive people, especially children and the elderly, investigating allergenicity of the pollen grains and aromatic petalsin plants that pollinatein the spring is necessary. Because the pollen grains of this plant are carried by bumblebees and wasps (21,24), it is possible that pollen grains containing allergen compounds used in honey production can enter the human body (8,25). Our research in 2014, showed allergenicity petals of old ontogenical (26).…”
Section: Introductionmentioning
confidence: 86%
“…This beautiful and extremely fragrant flower is native to Europe and North Africa and has subsequently spread to Asia (18)(19)(20). The flowering period is between the months of May and June (19)(20)(21)(22)(23)(24). Since seasonal sensitivities increase in the spring and allergic reactions occur in sensitive people, especially children and the elderly, investigating allergenicity of the pollen grains and aromatic petalsin plants that pollinatein the spring is necessary.…”
Section: Introductionmentioning
confidence: 99%